CFD Analysis of the Thermal-Hydraulic Performance of Traditional and Alternative Oils for Transformer Cooling - Elisabetta Salerno; Adriano Leonforte; Mattia Grespan; Diego Angeli; Mauro A. Corticelli (Applied Sciences)
The search for alternative, more environmentally friendly coolants to replace mineral oils in power transformers represents a relevant challenge for the power industry. In this frame, a CFD analysis is carried out by means of an open-source, conjugate heat transfer Finite Volume solver to assess the heat transfer performance of different coolants in a disc-type winding of an oil-immersed power transformer, whose geometry is taken from a reference case in the literature. Four different oils are considered: two mineral oils widely established among power transformer manufacturers, a synthetic ester and a natural ester. The latter two represent environmentally friendly alternatives to mineral oils, of great interest for the specific sector. The influence of temperature-dependent thermophysical properties on the overall flow and on the location and value of the hot spots in the copper conductors is discussed, highlighting the strength and weaknesses of the four oils as transformer coolants. In particular, the natural ester exhibits the best heat transfer performance, whereas high hot-spot temperatures and strong fluctuations are found for both mineral oils and the synthetic ester.